Integrating 21st-Century Skills into Instructional Materials for Sustainable Education - Pecson, Ryan; Sarmiento, Joshua (Indonesian Journal of Instructional Media and Model, 2024)
As transmitters of competencies, instructional materials or teaching and learning materials (TLM) ensure that quality education transpires among learners. As education and learners evolve, the use of diversified, interactive, flexible, inclusive, and learner-centered instructional materials is becoming more and more relevant. With that in mind, the present study determines the perceptions of educators in various academic institutions on the needed 21st-century skills in developing instructional materials for learners to sustain high-quality instructional practice. It uses the descriptive survey design of quantitative research to survey key information about 39 purposively selected educators in various provinces in the Philippines who responded to a structured questionnaire, wherein the results are treated using descriptive statistics. The findings underscore the need to integrate a broad range of 21st-century skills into instructional materials to prepare learners for modern complexities. Based on expert educators' insights, this study offers a comprehensive list of instructional materials for such integration and highlights the importance of educators' proficiency in selecting and utilizing these materials. Future research can explore the effectiveness of innovative instructional materials in cultivating these skills.